INSPECTORATE SUPERVISION PERFORMANCE IN THE UTILIZATION OF BOS FUNDS IN THE PROVINCE OF SOUTH SUMATRA IN 2022 - Vibio Pratama, M. Fernanda; Kariem, M. Quranul; Febriyanti, Doris (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2022)
This study describes the school operational assistance program (bos) which is a government program that basically provides funding for non-personnel operating costs for basic education units as implementers of the compulsory education program. According to PP Number 48 of 2008, what is meant by "non-personnel costs" are costs for consumable educational materials or equipment, and indirect costs in the form of power, water, telecommunications services, maintenance of facilities and infrastructure, overtime pay, transportation, consumption, taxes, and others. The results of this study are that the inspectorate has the characteristics/pattern of supervision related to boss funds which are internal, preventive, repressive, direct, indirect, and formal. In assisting the inspectorate task indirectly the 3 Palembang State High School Committee.